SELEKTIVITAS ANTIKANKER EKSTRAK DAUN SIRSAK (Annona muricata) PADA LINI SEL KANKER PAYUDARA - Dina Fatmawati; Suparmi Suparmi; Iwang Yusuf; Israhnanto Isradji (BIO-SITE |Biologi dan Sains Terapan, 2018)
Studies have been conducted on cytotoxicity of sirsak (Annona muricata) against T47D cell line. However, the selectivity of Annona muricata leaf extract against MCF-7 breast cancer has not established. This study aimed to determine the index selectivity of Annona muricata leaf extract against MCF-7 breast cancer cell line. In this quasy experimental study using 2 kind of cell line, The MCF-7 breast cancer cell line and Vero cell line as normal cell were treated with Annona muricata leaf extract at dose 1000, 500, 250, 125, 62.5, 31.5 µg/mL respectively. The MTT assay were used to evaluate the viability of both cell line after treatment with Annona muricata leaf extract. The data of viability cells were analyzed with Probit regression to determine the IC50 value of Annona muricata leaf extract in both cell lines. The selectivity of two treatment was determine based on the selectivity index (SI) that represents the ratio of IC50 value of Annona muricata leaf extract. The IC50 value of MCF-7 and normal cell were 44.94 and 184.04 respectively with selectivity index 4. This result suggested that Annona muricata had cytotoxic effect in MCF-7 breast cancer cell line but not in normal cells. In conclusion Annona muricata leaf extract has cytotoxic effect to MCF7 breast cancer cell selectively.